Effect of an Exogenous Protease in Association with Carbohydrases in Broilers Infected with Coccidia - Caldas, J.V.; Sabir, M.A.; Putsakum, M.; England, J.A.; Coon , C.N. (International Journal of Poultry Science, 2016)
Background: Live coccidiosis vaccines given to broilers at hatch generally decrease body weight gain during the early feeding phases but the effect could reverse after the development of immunity. This study intended to determine if diets supplemented with exogenous protease and carbohydrases can improve Body Weight Gain (BWG) and Feed Conversion Ratio (FCR) after coccidia infection. Methodology: Two thousand three hundred and four male chicks were randomly divided into six diets: Negative Control (NC), Positive Control (PC) and 4 multi-enzyme composites (MEC), all enzyme diets had protease but different carbohydrase combinations for 42 days study. The ANOVA test was utilized. Results: Three different MEC decreased the E. coli population in the ileum. Diets with MEC provided an additional apparent metabolizable energy corrected by nitrogen (AMEn) from 91-236 kcal kg–1 compared to the NC and improved digestibility of Amino Acids (AA) from 0.86-5.53% for 3 of the MEC. Cystine, threonine and serine digestibility were each increased >2.8% with MEC compared to the NC. Proteins in mucins contain high quantities of these AA, so enzymes may be providing more of these AA. The FCR for NC broilers was worse than PC (p≤0.05). The FCR, tended to be improved with three of the MEC, however one composite did not achieve better FCR. Conclusion: The MEC improved nutrient utilization with tendency to improve FCR. However, more time may be required to achieve compensatory BWG using MEC with a coccidia infection. The present study also opens the door to study the interaction of MEC and microflora population in the gastrointestinal tract of chickens.